W. G. SEBALD: THE PLEASURE AND PAIN OF BEAUTY - Duttlinger, C (2009)
Beauty plays a central but ambivalent role in Sebald's writings. Echoing Kant's aesthetic theory, Sebald's texts emphasise the disinterested and free nature of aesthetic pleasure, but they also argue that this pleasure is increasingly threatened in the modern age, as the human relationship towards nature becomes informed by a desire for domination and exploitation. In a cross-reading of Sebald's literary works and his essays on Adalbert Stifter and Gottfried Keller, this article shows how Sebald's own texts attempt to resist this development. By highlighting the beauty of the natural world, they prepare the ground for renewed appreciation, but also for encounter and compassion. Yet the beauty thus displayed is often situated within the context of suffering and death, and by depicting it, Sebald's texts risk becoming complicit with the very structures which they try to undermine. A similar complicity between pleasure and domination also shapes the realm of man-made artefacts. Sebald's texts attempt to escape this double-bind in passages which abandon conventionally realist representation in favour of more abstract tableaux of beautiful patterns and colours. This movement towards abstraction serves to shield beauty from the dictates of instrumental reason, fostering an aesthetic pleasure which remains open to compassion. © 2009 Blackwell Publishing Ltd.